\(\frac{2}{3}\left(x-1\right)+\frac{4}{7}\left(2x-3\right)=\frac{1}{21}\left(x-6\right)\)
\(\frac{2}{3}x-\frac{2}{3}+\frac{8}{7}x-\frac{12}{7}=\frac{1}{21}x-\frac{6}{21}\)
\(\frac{2}{3}x+\frac{8}{7}x-\frac{1}{21}x=\frac{2}{3}+\frac{12}{7}-\frac{6}{21}\)
\(\frac{14}{21}x+\frac{24}{21}x-\frac{1}{21}x=\frac{14}{21}+\frac{36}{21}-\frac{6}{21}\)
\(x\left(\frac{14}{21}+\frac{24}{21}-\frac{1}{21}\right)=\frac{14+36-6}{21}\)
\(\frac{37}{21}x=\frac{44}{21}\)
\(x=\frac{44}{21}:\frac{37}{21}=\frac{44}{37}\)